Longitudinal Evaluation of Clinical Decision Support to Improve Influenza Vaccine Uptake in an Integrated Pediatric Health Care Delivery System, Houston, Texas - Bratic, Julia S.; Cunningham, Rachel M.; Belleza-Bascon, Bella; Watson, Scott K.; Guffey, Danielle; Boom, Julie A. (Applied Clinical Informatics, 2019)
Objective Our study retrospectively evaluated the implementation of an influenza vaccine best practice alert (BPA) in an electronic medical record within an integrated pediatric health care delivery system.Methods An influenza BPA was implemented throughout a large pediatric health care delivery system in Houston, TX, to improve vaccine uptake. Outcomes were measured retrospectively over 3 years of BPA implementation and compared with a control year prior to BPA implementation. Primary outcomes were influenza vaccine uptake, distribution of influenza vaccines ordered by week, proportion of BPA displays ignored, and missed vaccination opportunities.Results Influenza vaccine uptake declined from the pre-BPA year (47.2%; 95% confidence interval [CI]: 47.0, 47.4) to the last study year (45.1%; 95% CI: 44.9, 45.2). BPA displays were increasingly ignored by clinical staff throughout the study years from 59.6% in 2014–2015 to 72.5% in 2016–2017. For providers, BPA displays were ignored less frequently each year from 53.4% in 2014–2015 to 51.4% in 2017–2017. Within the primary care outpatient group, the proportion of missed vaccination opportunities in sick visits decreased from 86.8% during the pre-BPA year to 81.0, 79.8, and 82.7% during the subsequent study years 2014–2015, 2015–2016, and 2016–2017, respectively.Conclusion Implementation of a widespread influenza BPA in an integrated pediatric health care delivery system did not produce meaningful increases in influenza vaccine uptake. Differences between clinical staff and providers on BPA use warrant further investigation.
Keywords: best practice alert; influenza vaccine; clinical decision support; vaccine uptake